Why do rural communities do what they do in the context of livelihood activities? Exploring the livelihood priority and viability nexus. Issue 5 (20th October 2017) - Baffoe, Gideon; Matsuda, Hirotaka
Abstract: This study seeks to empirically understand why rural households do what they do in the context of livelihood activities, even though most of the activities are not economically viable. Mixed methods, including interviews and questionnaire survey ( n  = 200), were used to collect primary data. Findings showed that livelihood priority is not the same as economic viability. We argued that most livelihood related projects in rural communities tend to be either nonstarter or counterproductive because of the failure of development agents to separate priority from viability. A gender perspective is applied to understand the differences in livelihood participation as well as preferences among households. While female-headed households tend to favor livelihood activities with stable income, their male counterparts prefer activities with higher income, suggesting that the former tend to be more risk averse. Results suggest that policy aimed at improving livelihood activities in rural communities should focus on viable projects.